The promise of workplace training for non-college-bound youth : theory and evidence from German apprenticeship - Clark, Damon [Verfasser]; Fahr, Rene [Verfasser] (My University, 2001)
"This paper assesses the potential of 'workplace training' with reference to German Apprenticeship. When occupational matching is important, we derive conditions under which firms provide 'optimal' training packages. Since the German system broadly meets these conditions, we evaluate the effectiveness of apprenticeship using a large administrative dataset. We find returns to apprenticeship for even the lowest ability school-leavers comparable to standard estimates of the return to school, and show that training is transferable across a wide range of occupations, such as a one-digit occupation group. We conclude that the positive experience with German Apprenticeship Training may guide the design of similar policies in other countries." (Author's abstract, IAB-Doku) ((en))
Keywords: G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; Berufsausbildung; Betriebliche Berufsausbildung; Zwischenbetriebliche Mobilität; Berufliche Mobilität; Quantitative Angaben; 1975-1995